Perancangan Perbaikan Bisnis Proses Menggunakan Metode Business Process Improvement Pada Layanan Penerbitan Majalah (Studi Pada PT. East Java Liberty Coy) - Rista Yasin Lamohammad Hende; Nanang Yudi Setiawan; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PT.East Java Liberty Coy is one of the subsidiaries of Java Pos Group which is engaged in print media. In running the business process there are several problems that have the potential to disrupt the course of business activities. Unoptimal processes on PT.East Java Liberty Coy include data storage is not integrated or fragmented which can cause data duplication, data loss due to human error. So it is necessary to analyze the business processes that have been applied, and then evaluated to determine the business processes that have the potential to disrupt the course of organizational activities in order to provide recommendations in the form of business process improvement recommendations. This research uses Business Process and Notation notation (BPMN) and Business Process Improvement (BPI) as evaluation method. Method Business Process Improvement applied in this research from phase 1: organizing improvement, phase 2: understanding the process and phase 3: streamlining. From the simulation results The current business process and business process recommendations are found that the level of time analysis of business process renewal contract advertising recommendations obtained the effectiveness of time up to 82.46%. So it can be concluded that business process improvement can improve the performance to be more efficient and effective, hence the recommendation of this business process is important to be applied to PT. East Java Liberty Coy.